2014
DOI: 10.1177/0164027514545975
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Nursing Home Resident–Reported Quality of Life

Abstract: Improving quality of nursing homes (NHs) is a major social priority, yet few studies examine the role of facility characteristics for residents' quality of life (QOL). This study goes beyond cross-sectional analyses by examining the predictors of NH residents' QOL on the facility level over time. We used three data sources, namely resident interviews using a multidimensional measure of QOL collected in all Medicaid-certified NHs in Minnesota (N = 369), resident clinical data from the minimum data set, and faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 46 publications
3
50
1
Order By: Relevance
“…6 Family members do not just visit their relatives, but also engage in providing and managing body care, offering emotional support, promoting social engagement, overseeing the care provided by the staff, and contributing resources and ideas to the LTCF community. 7 Studies have shown that family involvement in residential long-term care may be related to resident outcomes. 8,9 Data from Canada have shown that over one-fifth of family members assist their relative in a facility providing >10 h of care per week, with the hours increasing when the resident was older or more ill. 10 However, communication among LTCF staff, residents and their family members remain ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…6 Family members do not just visit their relatives, but also engage in providing and managing body care, offering emotional support, promoting social engagement, overseeing the care provided by the staff, and contributing resources and ideas to the LTCF community. 7 Studies have shown that family involvement in residential long-term care may be related to resident outcomes. 8,9 Data from Canada have shown that over one-fifth of family members assist their relative in a facility providing >10 h of care per week, with the hours increasing when the resident was older or more ill. 10 However, communication among LTCF staff, residents and their family members remain ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis on HRQoL is important because the construct underscores this population’s perspectives about their well-being, which is affected both by changes in their health 12-14 and the quality of the LTSS they receive. 12,13,15,16 HRQoL is now recognized as a complex construct, encompassing multiple domains, including biological and physiological factors, symptom status, physical and cognitive functional status, general health perceptions, emotional status, social support and overall quality of life. 17 …”
Section: Introductionmentioning
confidence: 99%
“…The few reported longitudinal studies have focused on a single context (e.g., nursing homes) as the unit of analysis 16,23 , focused on a limited set of HRQoL domains 24 or were limited to a specific subgroup, commonly older adults with dementia. 16,25,26 …”
Section: Introductionmentioning
confidence: 99%
“…Based on ten individual studies assessing the relationship between registered nurses, certified nurse assistants or nurse aides and quality of life, we found no evidence of such a relationship (19)(20)(21)(22)(23)(27)(28)(29)(30)(31). Four studies considering the employment of activity staff found a (slight) positive relationship with residents' quality of life (19,(27)(28)(29).…”
Section: Educational Background Of Staff and Quality Of Lifementioning
confidence: 76%